2014
DOI: 10.1021/la502574p
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Self-Assembly of Gold and Silver Nanoparticles onto Thiophene Oil

Abstract: Nanoparticle self-assembly is fundamentally important for bottom-up functional device fabrication. Currently, most nanoparticle self-assembly has been achieved with gold nanoparticles (AuNPs) functionalized with surfactants, polymeric materials, or cross-linkers. Reported herein is a facile synthesis of gold and silver nanoparticle (AgNP) films assembled onto thiophene oil by simply vortex mixing neat thiophene with colloidal AuNPs or AgNPs for ∼1 min. The AuNP film can be made using every type of colloidal Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…129 When thiophene was used as the organic phase solution it was observed that the organic solvent was able to replacing some of the citrate particles adsorbed on the surface of the nanoparticles held at the interface resulting in the formation of a Janus particle structure. 45 These observations suggest that the assembly at the liquid/liquid interface may have a substantial influence on the ligand structure on the surface, indicating that some alteration of the surface chemistry may occur, driven by the reduction in surface energy. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50...…”
Section: Surface Enhanced Raman Scattering (Sers)mentioning
confidence: 95%
“…129 When thiophene was used as the organic phase solution it was observed that the organic solvent was able to replacing some of the citrate particles adsorbed on the surface of the nanoparticles held at the interface resulting in the formation of a Janus particle structure. 45 These observations suggest that the assembly at the liquid/liquid interface may have a substantial influence on the ligand structure on the surface, indicating that some alteration of the surface chemistry may occur, driven by the reduction in surface energy. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50...…”
Section: Surface Enhanced Raman Scattering (Sers)mentioning
confidence: 95%
“…26 Crucially for the production of optical technology, NP films (nanofilms) at liquid-liquid interfaces have been shown to remain stable for time periods ranging from months to years. 24,27 Since Yogev and Efrima 28 first described the formation of metal liquid-like films upon the reduction of silver salts at liquid-liquid interfaces, many other methods have been introduced to form such nanofilms, e.g. addition of ethanol or methanol to the interfacial region, 23,29,30 precise injection of colloidal AuNP solutions prepared in methanol at water-organic solvent interfaces, 31 use of salts, 32 solvent evaporation, 33 covalent bonding 14,34,35 and self-assembly provided by electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…An interface between two immiscible electrolyte solutions (ITIES) or a "soft" interface is an attractive platform at which to assemble nanoparticles (NPs) due to its electrochemical polarisability, inherent defect-free nature, mechanical flexibility and the ease with which NPs may be manipulated and precisely tuned therein [1][2][3][4][5][6][7][8]. A burgeoning area of research is concerned with the biphasic electrocatalysis of redox reactions of interest for energy research, including the oxygen (O 2 ) reduction reaction (ORR) [9][10][11][12][13][14][15][16][17][18][19] and the hydrogen (H 2 ) evolution reaction (HER) [20][21][22][23][24][25][26][27][28], using soft interfaces functionalized with molecular species, metallic NPs or inorganic non-precious metal-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…Gold NPs (AuNPs) can be regarded as multivalent redox species with a wide range of oxidation states that may be charged or discharged by Fermi level equilibration with redox couples in solution [34]. Recently, we highlighted the use of soft interfaces functionalized with one AuNP thick "nanofilms" to catalyse IET between a lipophilic electron donor (D) redox couple, ferrocenium cation/ferrocene (Fc +/0 ), and a hydrophilic electron acceptor (A) redox couple, ferri/ferro-cyanide ([Fe(CN) 6 ] 3À/4À ) [8]. Similarly, Dryfe and co-workers catalysed IET between the same lipophilic electron donor and hydrophilic electron acceptor redox couples by functionalizing the soft interface with adsorbed conductive carbon nanomaterials, such as few-layer graphene and carbon nanotubes [35].…”
Section: Introductionmentioning
confidence: 99%